Development of an accurate nursing program based on function in chronic venous leg ulcers: protocol for matching function status with nursing interventions using the Delphi survey - Tang Yi-Fan; Hu Xin-Yu; Zhao Jing; Gu Ze-Juan; Xing Shuang-Shuang; Wang Wei-Yun (Sciendo, 2018)
Venous leg ulceration (VLU) is one of the complications of lower extremity venous reflux and reflux disorder of severe diseases, with many adverse effects on patient's work and life. Nowadays, more and more patients with VLU accept wound care in community setting. Clinical nurses generally take care of the patients based on their own experiences. Healing in VLU is an incredibly complex process, which puzzles even experts. The majority of general nurses do not have this level of expertise, especially those nurses serving in community. Function is the basis of nursing activities. Patients always show different clinical manifestations and self-care abilities due to various function states, which cannot be reflected completely by the existing nursing practice. How to describe nursing practice standardized in order to demonstrate the effectiveness of interventions and facilitate interdisciplinary communication is another urgent problem. Therefore, the aim of this project is to develop an accurate nursing program based on function in chronic venous leg ulcers, which can both satisfy the needs of patients and promote nursing revolution.